Stress Coping Strategy pada Mahasiswa yang Bekerja - Adinda Prameswari; Wa Ode Suarni; Yuliastri Ambar Pambudhi (Jurnal Sublimapsi, 2023)
Individuals in dealing with stress automatically form a stress coping strategy against themselves to try to manage the distance that exists between demands, both from themselves and from the environment that is considered heavy and exceeds the individual's capacity. This study aims to determine the source of stress (stressor) students who work and determine the stress coping strategy of students who work. This study took 3 subjects with purposive sampling technique. This study uses a qualitative method with a descriptive narrative approach. Collecting data using interviews and observation. The results showed that students who worked did stress coping strategies in the form of problem focused coping and emotional focused coping. Problem focused coping, the three subjects sought social support by seeking help or asking for advice from those closest to them on the problems they faced. Subject I also had a confrontation, while subject II and subject III did not. Emotional focused coping, the three subjects did self control, positive reappraisal, and accepting responsibility. Subject I also did escape/avoidance, while subject II and subject III did not.